Molecular phylogeny of Nearctic proteocephalids of the Proteocephalus-aggregate (Cestoda: Onchoproteocephalidea) - Uhrová, Lucie (Jihočeská univerzita, 2020)
Phylogenetic relationships of species of the Proteocephalus-aggregate, a group of proteocephalidean tapeworms from freshwater teleosts with Holarctic distribution, were evaluated with emphasis on enlarged sampling of representative taxa from the Nearctic region. Molecular Phylogenetic analyses based on 28S rDNA and cytochrome c oxidase subunit 1 supported validity of the newly sampled species and showed that Nearcitc species of the Proteocephalus-aggregate parasitizing common fish host groups share a common evolutionary history. In addition, the current molecular data are not capable of resolving internal phylogeny of the group and alternative molecular markers should be aimed in future phylogenetic treatments of the group.
Molecular phylogeny of Nearctic proteocephalids of the Proteocephalus-aggregate (Cestoda: Onchoproteocephalidea)
Keywords: Cestoda; Onchoproteocephalidea; molecular phylogeny; Proteocephalus-aggregate; Cestoda; Onchoproteocephalidea; molecular phylogeny; Proteocephalus-aggregate